Enhancing Adolescent Mental Health Literacy through a Community-Based Educational Approach in Islamic Boarding Schools - Dewi Kusumawati, Prima; Reni Nurhidayah; Dhita Kurnia Sari (Universitas STRADA Indonesia, 2025)
Adolescents in Islamic boarding schools (pesantren) often face mental health challenges while having limited access to relevant education and services. Mental Health Literacy (MHL) plays a crucial role in early recognition, stigma reduction, and appropriate help-seeking behavior. This study aimed to assess the effectiveness of a community-based mental health education intervention in improving mental health literacy among adolescents in an Islamic boarding school setting. A quasi-experimental one-group pretest-posttest design was conducted involving 80 students aged 13–18 years in Nganjuk, East Java. The intervention included video-based modules, peer discussions, and counseling facilitated by school health units (UKS) and mental health cadres. The Adolescent Mental Health Literacy Questionnaire (AMHLQ) was used to measure knowledge, attitudes, and mental health awareness before and after the intervention. Data were analyzed using paired t-tests. There was a significant improvement in mental health literacy scores from pretest (M = 64.75, SD = 7.42) to posttest (M = 78.63, SD = 6.98), with a t- count of 11.42 (p < 0.001). The intervention was effective in enhancing students’ understanding of mental health concepts, reducing stigma, and encouraging help- seeking behaviors. Factors such as age, gender, and length of stay in the pesantren may have influenced outcomes. Community-based, culturally tailored mental health education using multimedia and peer support significantly improves adolescent mental health literacy in Islamic boarding schools. Strengthening the role of school-based health units and digital tools is recommended for future mental health promotion in similar settings.